PENGARUH UKURAN PERUSAHAAN, LEVERAGE DAN PERSISTENSI LABA TERHADAP EARNINGS RESPONSE COEFFICIENT - Mutumanikam, Primadonna Ratna (Universitas Muhammadiyah Tangerang, 2021)
This research aims to analize the effect of firm size, leverage and earnings persistence to earnings response coefficient. The data in this research obtained from the annual report of financial statements in property and real estate companies listed in the Indonesian Stock Exchange period 2016-2018. The sample of this study are 29 companies which selected by using purposive sampling method from companies property and real estate listed in Indonesia Stock Exchange period 2016 until 2018. To tested the hypothesis, it is used by multiple regression analysis. The result of research show that: 1) there is no significant the effect of firm size to the company earnings response coefficient. 2) there is no significant the effect of leverage to the company earnings response coefficient. 3) there is positive and significant the effect of earnings persistence to the company earnings response coefficient.4) There is significant the simultaneous effect between firm size, leverage, earnings persistence and earning response coefficient